Effectiveness Model of the Nature Tourism Based Community Forest Program Implementation in Bangka Tengah District - Oktedy Andryansah; Dodik Ridho Nurrochmat; Nandi Kosmaryandi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Nature tourism-based community forest (NTCF) is one form of community forest utilization in Bangka Tengah District. In its implementation, the effectiveness of this program is relatively different among community forest groups. This difference of effectiveness level could be influenced by various factors. Therefore, identification of these factors needs to be taken into consideration in making decisions to improve the effectiveness of the intended program. This study aims to identify the influencing factors and efforts to improve the effectiveness of NTCF implementation. The method used is the structural equation modeling and qualitative analysis. The results of the study showed that the factors that influence the effectiveness of the implementation are the attitude of the government, attitudes of community leaders, forestry extension human resources, attitudes of non-governmental organizations and the level of education of the community. For these reasons, the efforts should be conducted to achieve the effectiveness of the NTCF are to increase the support of community leaders, NGOs, and the government, increase the capacity of human resources for forestry instructors and provide education and training for the groups with relatively low levels of education. Keywords: community forest, natural tourism, structural equation modeling, utilization